2017
DOI: 10.1016/j.jogc.2017.04.024
|View full text |Cite
|
Sign up to set email alerts
|

No. 225-Management Guidelines for Obstetric Patients and Neonates Born to Mothers With Suspected or Probable Severe Acute Respiratory Syndrome (SARS)

Abstract: Objective: This document summarizes the limited experience of SARS in pregnancy and suggests guidelines for management.Outcomes: Cases reported from Asia suggest that maternal and fetal outcomes are worsened by SARS during pregnancy.Evidence: Medline was searched for relevant articles published in English from 2000 to 2007. Case reports were reviewed and expert opinion sought.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(81 citation statements)
references
References 34 publications
3
73
0
5
Order By: Relevance
“…According to the No. 225 Management Guidelines for Obstetric Patients and Neonates Born to Mothers With Suspected or Probable SARS [16], we took strict measures to reduce the risk of infection. The male infant in the case reported was delivered by emergency cesarean under contact, droplet, and airborne transmission precautions [17].…”
Section: Discussionmentioning
confidence: 99%
“…According to the No. 225 Management Guidelines for Obstetric Patients and Neonates Born to Mothers With Suspected or Probable SARS [16], we took strict measures to reduce the risk of infection. The male infant in the case reported was delivered by emergency cesarean under contact, droplet, and airborne transmission precautions [17].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical outcomes among pregnant women with SARS in Hong Kong were worse than those occurring in infected women who were not pregnant [32]. Wong et al [29] evaluated the obstetrical outcomes from a cohort of pregnant women who developed SARS in Hong Kong during the period of 1 February to 31 July 2003.…”
Section: Sars and Pregnancymentioning
confidence: 99%
“…Maxwell et al [32] reported 7 pregnant women infected with SARS-CoV who were followed at a designated SARS unit-2 of the 7 died (CFR of 28%), and 4 (57%) required ICU hospitalization and mechanical ventilation. In contrast, the mortality rate was less than 10% and mechanical ventilation rate less than 20% among non-pregnant, age-matched counterparts who were not infected with SARS-CoV.…”
Section: Sars and Pregnancymentioning
confidence: 99%
“…Two infected mothers recovered and maintained their pregnancy but had infants with intrauterine growth restriction (IUGR). Among the live newborn infants, none had clinical or laboratory evidence for SARS-CoV infection [18]. Ng et al, in a study evaluated the placental pathology in seven pregnant women infected with SARS-CoV.…”
Section: Mers-cov or Sars-covmentioning
confidence: 99%